Faktor yang Mempengaruhi Persepsi Orang Tua dalam Penerimaan Vaksinasi Covid-19 pada Remaja Usia 12 – 17 Tahun di Wilayah Kerja Puskesmas Rajabasa Indah - Nurfauzi, M. Rizal; Yulyani, Vera; Triwahyuni, Tusy; Kurniati, Mala (Universitas Malahayati, 2023)
ABSTRACT Covid-19 vaccination is one of the government's programs in dealing with the Covid-19 pandemic in Indonesia. Vaccination in adolescents is influenced by parents' perceptions in decision making. Adolescent vaccination achievements in the Lampung region are still very low. this study aims to identify factors that influence parents' perceptions of receiving Covid-19 vaccinations for adolescents aged 12-17 years in the working area of the Rajabasa Indah Health Center in 2022. Quantitative study with an analytic approach using a cross-sectional and the instrument used is a questionnaire This type of research is a descriptive quantitative research with a cross-sectional design, with purposive sampling technique. The number of samples studied was 395 parents who had children aged 12-17 years. Data analysis was performed by Chi-square test. It is known that there is a relationship between parents' perceptions and perceived vulnerability (p=0.044), parents' perceptions and perceived benefits (p=0.043), and parents' perceptions with perceived barriers (p=0.05) towards receiving the Covid-19 vaccination in adolescents aged 12-17 years. Of the 5 parents' perceptions regarding the factors that influence acceptance of the Covid-19 vaccine for adolescents aged 12-17 years. There are only 3 acceptable factors, namely the vulnerability of Covid-19 vaccination, the benefits of Covid-19 vaccination, and the inhibition of Covid-19 vaccination on the accessibility of Covid-19 vaccination in adolescents aged 12-17 years. Therefore, it is necessary to make efforts to increase information and education about the Covid-19 vaccine to parents and the general public so that they can increase acceptance of Covid-19 vaccination in adolescents. Keyword: Covid-19 Vaccination, Parents, Adolescents. ABSTRAK Vaksinasi Covid-19 menjadi salah satu program pemerintah dalam menangani pandemi Covid-19 di Indonesia. Vaksinasi pada remaja dipengaruhi oleh persepsi orang tua dalam pengambilan keputusan. Capaian vaksinasi remaja di wilayah Lampung masih sangat rendah. penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi persepsi orangtua dalam menerima vaksinasi Covid-19 untuk remaja usia 12-17 tahun di wilayah kerja Puskesmas Rajabasa Indah pada tahun 2022. Jenis penelitian ini adalah kuantitatif deskriptif dengan rancangan cross sectional, dengan teknik pengambilan sampel Purposive Sampling. Jumlah sampel yang diteliti sebanyak 395 orang tua yang memiliki anak usia 12- 17 tahun. Analisis data dilakukan dengan uji Chi-square. Diketahui terdapat hubungan persepsi orang tua dengan kerentanan yang dirasakan (p=0.044), persepsi orang tua dengan manfaat yang dirasakan (p=0.043), dan persepsi orang tua dengan hambatan yang dirasakan (p=0.05) terhadap penerimaan vaksinasi Covid-19 pada remaja usia 12-17 tahun. Dari 5 Persepsi orang tua mengenai faktor yang mempengaruhi penerimaan vaksinasi Covid-19 terhadap remaja usia 12-17 tahun. Hanya terdapat 3 faktor yang dapat diterima yaitu kerentanan vaksinasi Covid-19, manfaat vaksinasi Covid-19, dan hambatan vaksinasi Covid-19 terhadap penerimaan vaksinasi Covid-19 pada remaja usia 12-17 tahun. Oleh karena itu, perlu dilakukan upaya untuk meningkatkan informasi dan edukasi tentang vaksinasi Covid-19 kepada orang tua dan masyarakat secara umum agar dapat meningkatkan penerimaan vaksinasi Covid-19 pada remaja. Kata Kunci: Vaksinasi Covid-19, Orang Tua, Remaja